Author Correction: Major lung complications of systemic sclerosis. Issue 11 (November 2018) - Denton, Christopher; Wells, Athol; Coghlan, John
Corrections: Table 2: the text 'Also licensed for CTEPH; cannot be combined with a PDE5 inhibitor' has been moved to a different row; reference for this moved statement updated.